Rent Seeking: The Social Cost of Contestable Benefits - Arye L. Hillman; Ngo Van Long (Center for Economic Studies and ifo Institute (CESifo), 2017)
A major contribution of the public-choice school is the recognition by Gordon Tullock that contestable rents give rise to social losses because of unproductive resource use. Contestable rents usually are politically assigned privileges. Contestable rents can also be found outside of government decisions. We describe the example of rents in academia in different cultures. The primary empirical question regarding rent seeking concerns the magnitude of the social loss from the contesting of rents. Direct measurement is impeded by lack of data and indeed denial that rent seeking took place. Contest models provide guidance regarding social losses. We provide a generalized contest model. Social losses from rent seeking are diminished in high-income democracies because rent seeking usually takes place by groups seeking `public good' benefits. Rents are also less visible in democracies, because political accountability requires that rents be assigned in indirect non-transparent ways. These restraints are not present in autocracies, where rent seeking is also facilitated by corruption and by the need to influence a smaller number of decision makers. Ideology can influence whether rent seeking is recognized to exist.
Keywords: H00; 330; rent seeking; contests; political discretion; academic merit; ideology; political correctness